SOX2+ cell population from normal human brain white matter is able to generate mature oligodendrocytes. - Jorge Oliver-De La Cruz; Josefa Carrión-Navarro; Noemí García-Romero; Antonio Gutiérrez-Martín; Elisa Lázaro-Ibáñez; Carmen Escobedo-Lucea; Rosario Perona; Cristobal Belda-Iniesta; Angel Ayuso-Sacido (PLoS ONE, 2014)
OBJECTIVES: A number of neurodegenerative diseases progress with a loss of myelin, which makes them candidate diseases for the development of cell-replacement therapies based on mobilisation or isolation of the endogenous neural/glial progenitor cells, in vitro expansion, and further implantation. Cells expressing A2B5 or PDGFRA/CNP have been isolated within the pool of glial progenitor cells in the subcortical white matter of the normal adult human brain, all of which demonstrate glial progenitor features. However, the heterogeneity and differentiation potential of this pool of cells is not yet well established. METHODS: We used diffusion tensor images, histopathology, and immunostaining analysis to demonstrate normal cytoarchitecture and the absence of abnormalities in human temporal lobe samples from patients with mesial temporal sclerosis. These samples were used to isolate and enrich glial progenitor cells in vitro, and later to detect such cells in vivo. RESULTS: We have identified a subpopulation of SOX2+ cells, most of them co-localising with OLIG2, in the white matter of the normal adult human brain in vivo. These cells can be isolated and enriched in vitro, where they proliferate and generate immature (O4+) and mature (MBP+) oligodendrocytes and, to a lesser extent, astrocytes (GFAP+). CONCLUSION: Our results demonstrate the existence of a new glial progenitor cell subpopulation that expresses SOX2 in the white matter of the normal adult human brain. These cells might be of use for tissue regeneration procedures.